METODE GURU PAI DALAM MENINGKATKAN KARAKTER TOLERANSI SISWA DI SMK HARAPAN BANGSA PANTI KECAMATAN PANTI KABUPATEN PASAMAN - Mardawiyah; Fauzan; Alimir; Jasmienti (KOLONI, 2022)
The background of this research is that students in SMK Class XI have a good habit of greeting when entering class, for example if the teacher greets Muslim students to non-Muslim students, the teacher says good morning, this is true for both teachers and students. In addition, before starting the lesson, students always pray together with their beliefs according to their respective beliefs. In SMK, students are able to apply an attitude of religious tolerance in interacting at school, for example they do not make groups in school based on race, ethnicity and religion. With these differences, students can respect each other and students can also respect each other between friends of different religions. The approach used in this research is a qualitative approach, namely research that is not interested in testing certain hypotheses, but only describes what a variable is. The key informants in this study were PAI teachers at Harapan Bangsa Panti Vocational School, while the supporting informants were students of class XI. Data collection techniques using observation and interview techniques. Based on the findings of data analysis, several conclusions can be drawn, namely the PAI teacher method in increasing the tolerance character of students in class XI Vocational Schools, the hope of the nation in the Pasaman District is quite good, it can be seen from the way students speak politely to teachers and peers, respect and respect each other. other. In addition, students are able to apply an attitude of religious tolerance in interacting at school. They do not make groups in school based on race, ethnicity and religion, for example in play groups, they can hang out with friends who are not of the same religion, such as Christian students can hang out with friends who are Muslim and they try to relate to each other without discriminating against religion, tribes and others. With these differences, students can respect each other and students can also respect each other between friends of different religions. Keyword: PAI Teacher Method, Tolerance Character Education